Management of the Semester Credit System (SKS) Program in the Merdeka Curriculum at MAN 2 Pekanbaru City - Rezi Yunizahri; M. Jaya Adi Putra; Gimin Gimin (FKIP - Universitas Riau, 2026)
This study aims to determine the management function of the SKS program indicators in the Merdeka Curriculum at MAN 2 Pekanbaru City. This type of research is descriptive qualitative research with data collection techniques through documentation, observation and interviews. The data analysis technique of this research uses the Miles and Huberman model. The results of this study include 1) planning the SKS program at MAN 2 Pekanbaru City including holding meetings, preparing planning documents, mapping students and socializing the SKS program. 2) the organization of the SKS program at MAN 2 Pekanbaru City includes the appointment of the SKS program implementation team, as well as the division of tasks and their respective roles. 3) the implementation of the SKS program at MAN 2 Pekanbaru City includes using the Merdeka Curriculum with a differentiated learning process and providing learning services according to their respective abilities. 4) controlling the SKS program at MAN 2 Pekanbaru City, including the relevance of the SKS program to the vision and mission of the madrasah, supervision is carried out by madrasah supervisors, madrasah heads and deputy heads of academic fields to ensure that the SKS program is implemented according to implementation guidelines and summative and formative assessments are carried out as a form of student learning outcomes.